Correlation between serum vitamin D level and neonatal indirect hyperbilirubinemia - Shahrokh Mehrpisheh; Azadeh Memarian; Abolfazl Mahyar; Negin Sadat Valiahdi (BMC, 2018)
Abstract Background Considering the significant prevalence of Neonatal Indirect Hyperbilirubinemia (NIH) and its irreversible neurological complications, identifying the factors involved in the prevalence of neonatal jaundice is essential. The present study was conducted to determine the relationship between serum vitamin D levels and the prevalence of NIH in infants admitted to Qods Hospital of Qazvin in Iran in 2015-16. Methods In this case-control study, 30 term infants with NIH (the case group) were compared with 30 healthy, non- icteric, term infants (the control group) in terms of serum levels of 25-hydroxyvitamin D. The results were analyzed and compared between the two groups using t-test and the Chi-square test. Results The mean and standard deviation of serum 25-hydroxyvitamin D levels were 10.76 ± 8.6 ng/dl in the case group and 14.88 ± 11.38 ng/dl in the control group. There were no significant differences between the two groups (P = 0.11). Conclusion The results suggest the lack of a relationship between vitamin D levels and NIH. However, further prospective studies are needed to conclude that vitamin D has no role in the pathogenesis of NIH.